Renewable energies in EU transport - Kiss, Lívia Benita; Poór, Judit; Pintér, Ákos; Hollósy, Zsolt (Studia Mundi – Economica, 2021)
Transport is an important sector of the European Union’s economy and plays a vital role in today’s mobile society. It has set a target of 10% for the share of energy from renewable sources in transport by 2020. The share of energy from renewable sources used in transport increased from 1.5% in 2004 to 8.9% by 2019. However, each Member State has a different position. In Sweden (30.3%) and in Finland (21.3%) the rate is outstanding, nevertheless Netherlands exceeded the EU target by 2019, ahead of Austria, which was still in third place in 2018. Despite the fact that a few member states are now approaching the 8-9% share, in several member states the value is still relatively low: in Cyprus the share increased last year from 2.7% to 3.3%, while the value of Greece and Lithuania stagnated around 4.0-4.3% in the last 3 years. Due to the mandatory 2020 target, the production of liquid biofuels in the EU has increased significantly. Biodiesel is the most widely produced liquid biofuel. Liquid biofuels blended with fossil fuels are the most common renewable energy source in transport. In 2017, the largest ethanol and biodiesel producers in the EU were Germany, France and Poland. Transport is the second largest sector, contributing to CO2 emissions worldwide and accounting for more than a third of total energy consumption. Despite reduction efforts, CO2 emissions from European road transport have continued to rise. Transport is one of the sectors of energy consumption where the presence of renewable energy is lower and its growth is difficult to achieve, especially in countries that import all fuels in this way.